2017
DOI: 10.3847/1538-4357/aa6af8
|View full text |Cite
|
Sign up to set email alerts
|

The Sirius System and Its Astrophysical Puzzles: Hubble Space Telescope and Ground-based Astrometry

Abstract: Sirius, the seventh-nearest stellar system, is a visual binary containing the metallic-line A1V star SiriusA, the brightest star in the sky, orbited in a 50.13year period by SiriusB, the brightest and nearest white dwarf (WD). Using images obtained over nearly two decades with the Hubble Space Telescope (HST), along with photographic observations covering almost 20 years and nearly 2300 historical measurements dating back to the 19th century, we determine precise orbital elements for the visual binary. Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(55 citation statements)
references
References 76 publications
4
49
0
2
Order By: Relevance
“…The vast majority of WD masses cannot be measured directly, but have to be inferred from model-dependent determinations of their surface gravities and estimates of their radii from parallax determinations and photometric or spectroscopic flux measurements (44), or from gravitational redshifts in cases where the true radial velocity of the WD is known from measurements of a companion star (45). The number of WDs whose masses and radii have been directly measured with sufficient precision to test theoretical MRRs includes just three WDs in nearby wide visual binaries [Sirius B (46), Procyon B (47) and 40 Eri B (43)] and about 10 WDs in short-period eclipsing binaries (44). However the stars in the latter group have undergone common-envelope events and have therefore not evolved in the same way as isolated single stars.…”
Section: Astrophysics Of the Cool White Dwarf Stein 2051 Bmentioning
confidence: 99%
“…The vast majority of WD masses cannot be measured directly, but have to be inferred from model-dependent determinations of their surface gravities and estimates of their radii from parallax determinations and photometric or spectroscopic flux measurements (44), or from gravitational redshifts in cases where the true radial velocity of the WD is known from measurements of a companion star (45). The number of WDs whose masses and radii have been directly measured with sufficient precision to test theoretical MRRs includes just three WDs in nearby wide visual binaries [Sirius B (46), Procyon B (47) and 40 Eri B (43)] and about 10 WDs in short-period eclipsing binaries (44). However the stars in the latter group have undergone common-envelope events and have therefore not evolved in the same way as isolated single stars.…”
Section: Astrophysics Of the Cool White Dwarf Stein 2051 Bmentioning
confidence: 99%
“…Fundamental stellar parameters of Sirius A are taken from measured constraints on the angular diameter and bolometric flux (Davis et al 2011) together with the trigonometric parallax and dynamical mass (Bond et al 2017) from its orbit about Sirius B. For the model, we adopt an effective temperature of T ef f = 9843 K, a surface gravity of log(g)=4.28, and a radius of 1.71 R .…”
Section: Phoenix Modelmentioning
confidence: 99%
“…Sirius A is a 225 -250 Myr A1Vm star (Adelman 2004;Liebert et al 2005;Bond et al 2017) that has no observed circumstellar debris. Located only 2.64 ± 0.01 pc (van Leeuwen 2007) from our Solar System, this bright star is an excellent target to observe and model the submm-cm stellar emission of A-type stars.…”
Section: Introductionmentioning
confidence: 99%